Acute irritant threshold correlates with barrier function, skin hydration and contact hypersensitivity in atopic dermatitis and rosacea. Issue 11 (29th October 2013) - Darlenski, Razvigor; Kazandjieva, Jana; Tsankov, Nikolai; Fluhr, Joachim W.
Abstract: The aim of the study was to disclose interactions between epidermal barrier, skin irritation and sensitization in healthy and diseased skin. Transepidermal water loss (TEWL) and stratum corneum hydration (SCH) were assessed in adult patients with atopic dermatitis (AD), rosacea and healthy controls. A 4‐h patch test with seven concentrations of sodium lauryl sulphate was performed to determine the irritant threshold (IT). Contact sensitization pattern was revealed by patch testing with European baseline series. Subjects with a lower IT had higher TEWL values and lower SCH. Subjects with positive allergic reactions had significantly lower IT. In AD, epidermal barrier deterioration was detected on both volar forearm and nasolabial fold, while in rosacea, impeded skin physiology parameters were observed on the facial skin only, suggesting that barrier impediment is restricted to the face in rosacea, in contrast with AD where the abnormal skin physiology is generalized.